Experience-dependent neural plasticity is sensitive to shape of pitch contours - Chandrasekaran, Bharath (Neuroreport, 2007)
Language experience is known to modulate the preattentive processing of linguistically relevant pitch contours when presented in the speech domain. To assess if experience-dependent effects are specific to speech, we evaluated the mismatch negativity response to nonspeech homologs (iterated rippled noise) of such curvilinear pitch contours (Mandarin: Tone 1, ‘high level’; Tone 2, ‘high rising’) by Chinese and English listeners as well as to a pitch contour that was a linear approximation of Tone 2 (‘linear ascending ramp’). Mandarin speakers showed larger mismatch negativity responses than English to the curvilinear pitch contours only. These results suggest that experience-dependent neural plasticity in early cortical processing of linguistically relevant pitch contours is sensitive to naturally occurring pitch dimensions but not specific to speech per se.